Tax on consequences of civil law transactions of selling purebred dogs - Marta Sagan (Prawo Budżetowe Państwa i Samorządu)
This article is focused on tax on consequences of civil law transactions of selling purebred dogs. The analysis is based on the catalogue of activities which are subject to taxation under the tax on civil law transactions and provisions of the Animal Protection Act and the Civil Code. The Author claims that the contract for the sale of a purebred dog, a contract which is a civil law transaction, falls under the tax on civil law transactions. The subject of taxation with the tax on civil law transactions is, inter alia, a contract for the sale of goods and in matters not regulated in the Animal Protection Act (in the unregulated area there is, among others, an issue of trade in animals) the provisions on things shall apply accordingly to animals. In this article a lack of a legal definition of “purebred dog” – an issue important in the context of the subject of taxation – was also highlighted. However, due to the aforementioned lack of a definition doubts may arise when establishing criteria that will allow for an unambiguous determination when we are dealing with a purebred dog. In this text, a formal and dogmatic method was used in the research.